WELL-BEING Productivity and Happiness at Work - Johnson, Sheena (Springer International Publishing, 2018)
This book is the second edition of Well-being: Productivity and Happiness at Work that shows how to improve well-being in organizations. As with its predecessor, this new edition is remarkably timely. It explores the latest findings in the research on wellbeing and offers practical guidelines to the reader on how to promote well-being, productivity and happiness at work High levels of well-being at work are good for the employee and the organization. It means lower sickness-absence levels, better retention and more satisfied customers. People with higher levels of well-being live longer, pursue happier lives and are easier to work with. This updated edition provides an extensive overview of resilience at work and how this affects wellbeing. It introduces new topics such as what organizations need to consider about wellbeing in the context of an ageing workforce. It provides new case studies that have been conducted in the last few years including a case study on health a nd wellbeing in the Civil Service.